Pengaruh Siklus Hidup Perusahaan, Board Size, Sales Growth, Dividend Payment dan Research and Development Expenditure terhadap Cash Holding - Hidayah, Choirunina; Puspitasari, Windhy (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to analyze the influence of the company's life cycle, board size, sales growth, dividend payment, and research and development expenditure on cash holding. The data used in this study are secondary data sourced from the annual reports of manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2022. The research sample was selected using purposive sampling, resulting in 25 companies as samples. The data analysis method used for hypothesis testing is multiple linear regression using SPSS software. The research results indicate that the Company's Life Cycle has a positive influence on Cash Holding, while Board Size, Sales Growth, Dividend Payment, and Research and Development Expenditure have a negative influence on Cash Holding. This research is expected to be considered by management and investors to pay attention to the company's life cycle, board size, sales growth, dividend payment, and research and development in order to maintain cash holding stability and minimize losses. Keywords: Board Size, Cash Holding, Company Life Cycle, Dividend Payment, Research And Development Expenditure, Sales Growth.